Mapping and Improvement of Processes in the Public Sector: An Experience Report at the Public Ministry of Accounts of Pernambuco - Silva, Tony; Nascimento, Maria Gizele; Valença, George; Lira, Bruno; Fraga, Glória; Miranda, Luiz; Olivia, Márcia; Peixoto, Sérgio; Andrade, Ermeson (iSys - Journal of Information Systems, 2024)
The challenges inherent in the complexity of organizational processes, which involve several actors and stages, make improving these processes a challenging task, given the need to reconcile different perspectives and goals, in addition to the explanation of tacit procedures by interested parties. However, improving processes is crucial to the success of organizations. This study uses the Business Process Management methodology and the Business Process Model and Notation to present the experience of modeling and improving the Information Provision process at the Public Ministry of Accounts of the State of Pernambuco. The results show significant improvements, including knowledge management, rule detailing, standardization, efficient team sizing, categorization of demands, reduced duplicate requests, and reduced average response time, resulting in operational optimization and effectiveness. Hopefully, this experience report can encourage and benefit other organizations in their process mapping and improvement projects.